2006
DOI: 10.1016/j.jsgi.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plsma Visfatin Concentrations in Women With Gestational Diabetes Mellitus

Abstract: Our results show that there are decreased concentrations of plasma visfatin in gestational diabetes mellitus subjects and this may indicate that visfatin plays a role in the pathogenesis of gestational diabetes mellitus. However, further experiments are needed to clarify this role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 12 publications
4
86
2
1
Order By: Relevance
“…Therefore, mathematical models (HOMA vs IRI) used to calculate IR indices in pregnancy may give discrepant results, and thereby a relationship between visfatin and calculated IR indices. Very recently, unlike our findings and those by Krzyzanowska et al [9], Chan et al [10] have reported lower visfatin levels in women of Chinese origin with GDM. The precise reason for these differences is unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, mathematical models (HOMA vs IRI) used to calculate IR indices in pregnancy may give discrepant results, and thereby a relationship between visfatin and calculated IR indices. Very recently, unlike our findings and those by Krzyzanowska et al [9], Chan et al [10] have reported lower visfatin levels in women of Chinese origin with GDM. The precise reason for these differences is unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the study design by Chan et al was different: the time of GDM testing was about 24 instead of 28 weeks; different criteria were used to diagnose GDM; and no fasting or post-OGTT glucose values or insulin resistance parameters were assessed in their study. Furthermore, subjects of Far Eastern origin have significant differences in insulin sensitivity in comparison with subjects of Europid origin [11], and therefore it is not possible to directly compare the results of our study with the study by Chan et al [10].…”
Section: Discussionmentioning
confidence: 56%
“…These results are supported by Mazaki-Tovi et al [47] who obtained a comparable median visfatin concentration between normal and overweight pregnant women. On the other hand, lack of association between circulating visfatin and BMI was previously reported [49], although others reported positive [54] and negative [55] association between BMI and maternal visfatin. Other investigators could not demonstrate an association between visceral fat mass and plasma visfatin concentrations [56].…”
Section: Discussionmentioning
confidence: 86%
“…86 In contrast, the measurement of visfatin/PBEF in women with gestational diabetes indicated that this condition was characterized by lower circulating concentrations of the factor. 87 A genomic investigation revealed that variants in promoter sequence correlate with type-2 diabetes but not with measures of adiposity, 88 whereas a second study indicated significant association of promoter variants with fasting insulin. 89 The identification of visfatin/PBEF as an adipokine and its implication in diabetes is far from being universally accepted.…”
Section: Does Adiponectin Play An Essential Role In Ovarian/ Uterine/mentioning
confidence: 99%